Personality and coping in college students (2009)
The aim of this paper was to describe the personality traits and the coping styles used by 99 college students, and observe if this variable are related. The NEO Five Factor Inventory [NEO-FFI], and the Coping Strategies Questionnaire [CAE] was used. The results confirm that Neuroticism is related with passive and emotion focused coping strategies (maladaptive copings) whereas, Extraversion, Conscientiousness and Agreeableness are related with rational and active focused coping. Openness to Experience it was not associate with no one coping strategies. The findings provide evidence for the understanding of individual's differences about how the young people cope the several environment requests.